Estrategia de captación, para incrementar los niveles de fidelización de los clientes que acuden al hotel olímpico de la ciudad de Quevedo para el año 2012 - Rizzo Albán, Lizardo David (2012)
Qualified investigation " Strategy of capture, to increase the levels of loyalty of the clients who come to the Olympian Hotel of the city of Quevedo for the year 2012 ", approaches as problem " The offer of services ", characterized by a low performance, with which one has worked and, I am careless of the area of the marketing so necessary for the clients' capture, in these times where the competition is arduous. To give the solution to the problem, it was established as general aim " To design a Marketing plan for the clients' capture for the Olympian Hotel rested on aims that allowed to obtain the following results: Situational diagnosis of the company in mention. This obtained, across the direct observation, the analysis to his activities and countable and not countable records, and certainly to the application of the survey. Selection and methodological sustenance of the model of marketing plan who more adjusts to the needs of this organization. Here it was observed different models, from which the most relevant was chosen, for his later support in current bibliography and of quality. Development of the model and, I design diverse strategies of marketing, feasible of the loyalty of the clients being devoted and focused at obtaining. The results of the surveys were the point of item of this phase, since it was where the different needs and unsatisfied desires appeared, and immediately after which there were established strategies characterized by his competitiveness, which of being applied will give solution to his problems. Validation of the methodology proposed in the design of the Marketing plan for the company I object of study. It is necessary to emphasize also, that the executives and employees of the hotel in mention, collaborated unconditionally in the accomplishment of this work, on having shared his experiences and having remembered the complaints of his clients, besides which they allowed, that it was remaining inside his facilities while it realized the present investigative work